Pengembangan Media Pembelajaran Berbasis Android pada Mata Pelajaran Informatika - Rochma Ayustyaningtias; Enjang Alinurdin; Asep Wahyudin; Wahyudin Wahyudin (Journal on Education, 2025)
This study aims to develop and evaluate the effectiveness of an Android-based learning media to enhance students' understanding of digital literacy, particularly in distinguishing between facts and opinions. The learning media was developed using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. In the analysis stage, the software and hardware requirements were identified to support the media development. During the design stage, the media was created using Microsoft PowerPoint and iSpring Suite 11, with the content presented descriptively and in an easily understandable manner. The development stage produced media that was validated by experts, achieving scores of 88% for instructional design, 97% for content quality, and 92% for user experience, indicating excellent quality. The implementation was conducted in grade VIII at SMPN 43 Bandung, with the LORI questionnaire results showing an average score of 84.33%, indicating that the media is highly suitable for use in learning. The evaluation results demonstrated that the Android-based learning media is effective in helping students understand digital literacy and is highly suitable for classroom application.